2022
DOI: 10.1002/ange.202202633
|View full text |Cite
|
Sign up to set email alerts
|

Beyond a Linker: The Role of Photochemistry of Crosslinkers in the Direct Optical Patterning of Colloidal Nanocrystals

Abstract: Surface chemistry mediated direct optical patterning represents an emerging strategy for incorporating colloidal nanocrystals (NCs) in integrated optoelectronic platforms including displays and image sensors. However, the role of photochemistry of crosslinkers and other photoactive species in patterning remains elusive. Here we show the design of nitrene-and carbene-based photocrosslinkers can strongly affect the patterning capabilities and photophysical properties of NCs, especially quantum dots (QDs). Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Initially, we selected azides and benzophenone molecules reported in the literature as the photosensitive ligands on the surface of QD 16,17 . The efficiency of QLED devices assembled with photosensitive azide‐coated QDs decreased significantly after the exposure–development process, while the QDs coated with photosensitive benzophenone ligands tended to remain in adjacent sub‐pixels during the formation of full‐color patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we selected azides and benzophenone molecules reported in the literature as the photosensitive ligands on the surface of QD 16,17 . The efficiency of QLED devices assembled with photosensitive azide‐coated QDs decreased significantly after the exposure–development process, while the QDs coated with photosensitive benzophenone ligands tended to remain in adjacent sub‐pixels during the formation of full‐color patterns.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of achieving commercial application of a QLED display, the pixelation of QLED devices is a crucial step. However, the current research on pixelation of QLEDs mainly focuses on the emissive layer, , with limited studies on other functional layers. At the same time, if full-color QLED displays are to be realized, then the production process will inevitably face challenges in the pixelation of other functional layers.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work by Wulff and Chen have demonstrated that small-molecule bis­(diazirines), featuring two diazirine reactive units and either static or dynamic small molecules, can be used to cross-link polymeric mixtures (Figure B). In addition, a single tetrasubstituted diazirine derivative has been reported to give higher cross-linking efficiency when compared to disubstituted derivatives, though the synthesis and scalability of the tetra­(diazirine) presents challenges . This expanding family of diazirine cross-linkers has found application in a diverse range of fields, including plastic compatibilization, LED processing, , photopatterning, , and adhesives, among others. …”
Section: Introductionmentioning
confidence: 99%